A knowledge-based expert system for EIA using blackboard approach - Jazzar, Moneef Mohammad Abdel-Kareem; Daud, Mohamed; Bardaie, Mohd Zohadie; Ramli, Abd Rahman; Said, Salim (Faculty of Computer Science and Information Technology, University of Malaya, 1998)
Expert systems and knowledge-based systems are widely used in engineering applications and in problem-solving. Rapid development today has brought with it environmental problems that cause loss or destruction of natural resources. Environmental impact assessment (EIA) has been acknowledged as a powerful planning and decision-making tool to assess new development projects. It requires qualified personnel with special expertise and responsibility in their domain. Knowledge-based EIA systems incorporate expert’s knowledge and act as a device-giving system. The development of an expert system to produce environmental impact assessment reports using an intelligent blackboard co-operative approach is presented. The system has an advantage over human experts and can significantly reduce the complexity of a planning task like EIA.